1990
DOI: 10.1002/macp.1990.021911210
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion polymerization of styrene in the presence of poly(oxyethylene)‐poly(oxypropylene) block copolymers

Abstract: Poly(oxyethylene)-bl~k-poock-poly(oxypropylene~block-poly(oxyethylene) copolymers were applied as nonionic surfactants in styrene emulsion polymerization. The clouding phenomenon of the surfactant in the aqueous phase and the resulting characteristic partition of the block copolymer between aqueous and organic phase result b, two particularities of this system compared with classical emulsion polymerization: i) bimodal particle size distribution, and ii) unusual dependence of reaction rate on temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…As a consequence, phase inversion with the formation of a W/O/W multiple emulsion could occur, leading to a bimodal particle-size distribution for the latex, and the existence of two constant rate regions in a conversion vs. reaction time plot. This partition of the emulsifier and the formation of a bimodal size distributions was later on confirmed by Hergeth et al [95] These authors have further shown that the rate of polymerization, R p , as a function of the surfactant concentration is such that:…”
Section: Poly(alkylene Oxide) Block Copolymerssupporting
confidence: 48%
See 1 more Smart Citation
“…As a consequence, phase inversion with the formation of a W/O/W multiple emulsion could occur, leading to a bimodal particle-size distribution for the latex, and the existence of two constant rate regions in a conversion vs. reaction time plot. This partition of the emulsifier and the formation of a bimodal size distributions was later on confirmed by Hergeth et al [95] These authors have further shown that the rate of polymerization, R p , as a function of the surfactant concentration is such that:…”
Section: Poly(alkylene Oxide) Block Copolymerssupporting
confidence: 48%
“…-at around 50-60% conversion of the monomer, which typically corresponds to the disappearance of the emulsified monomer droplets, an increase of R p and of N p can often be noticed, especially for high monomer to copolymer ratios; this phenomena is typical for a droplet nucleation of latex particles as demonstrated by Ugelstad et al, [113] as well as for nucleation by nonionic surfactants partially solubilized in the monomer as shown by Hergeth et al; [95] in fact the copolymer, initially solubilized in the monomer droplets, promotes an additional nucleation and generates a second population of latex particles, -in the final stage, the polymerization is completed within the monomer swollen latex particles.…”
Section: Ps-peo Block Copolymersmentioning
confidence: 94%
“…Clearly, applying the emulsion polymerization technique to produce filled materials still presents great difficultacetate in the presence of highly dispersed quartz powder filler particles (''Suprasil'') was described by Hergeth et al ies. To obtain latex particles containing one, and only one, silica particle in the core, one must first avoid the formation (20)(21)(22)(23)(24). In these studies, the existence of an interfacial layer between the polymeric shell and the inorganic core of aggregates in the aqueous medium especially when the surface of the inorganic particles has been modified to render was proved by DSC and NMR measurements.…”
Section: Introductionmentioning
confidence: 98%
“…A traditional method of producing monocore composite particles is emulsion polymerization in the presence of inorganic particles [8][9][10][11][12][13][14][15][16][17]. With pretreatment comprising adsorption of hydroxypropylcellulose onto the silica particles for successive polymerization of styrene, Furusawa et al succeeded in preparing composite polystyrene latexes with a silica core [12].…”
Section: Introductionmentioning
confidence: 99%